2020
DOI: 10.3390/molecules25184068
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Production of Protein Hydrolysates from Monkfish By-Products: Chemical Features and Associated Biological Activities

Abstract: The aim of this work was the recovery of protein substrates from monkfish waste (heads and viscera) generated in the on-board processing of this species. Initially, the effect of pH, temperature, and protease concentration was studied on mixtures of a 1:1 ratio (w/v) of monkfish heads/water. The optimal conditions of proteolytic digestion were established at 57.4 °C, pH 8.31, [Alcalase] = 0.05% (v/w) for 3 h of hydrolysis. Later on, a set of hydrolysis at 5L-pH-stat reactor were run under the aforementioned co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 59 publications
2
20
1
Order By: Relevance
“…Digestibility and antihypertensive activity ( Table 4 ) appear correlated with the Mw of the hydrolysates, with more fragmented protein possessing higher digestibility and antihypertensive activity. However, previous studies have reported contradictory results, finding direct [ 45 ], inverse [ 46 ], or no relationship [ 29 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Digestibility and antihypertensive activity ( Table 4 ) appear correlated with the Mw of the hydrolysates, with more fragmented protein possessing higher digestibility and antihypertensive activity. However, previous studies have reported contradictory results, finding direct [ 45 ], inverse [ 46 ], or no relationship [ 29 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Digestibility and antihypertensive activity (Table 4) appear correlated with the Mw of the hydrolysates, with more fragmented protein possessing higher digestibility and antihypertensive activity. However, previous studies have reported contradictory results, finding direct [45], inverse [46], or no relationship [29,47]. Digestibility and antihypertensive activity (Table 4) appear correlated with the Mw of the hydrolysates, with more fragmented protein possessing higher digestibility and antihypertensive activity.…”
Section: Production Of Collagen Hydrolysates From Skin Waste After Gelatin Extractionmentioning
confidence: 89%
“…Digestibility and antihypertensive activity ( Table 7 ) appear correlated with the M w of the hydrolysates, with more fragmented protein possessing higher digestibility and antihypertensive activity. However, previous studies have reported contradictory results, finding direct [ 47 ], inverse [ 48 ], or no relationship [ 20 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sea bream Fish Scales [28] Alaska pollack (Theragra chalcogramma) Frame [29] Hoki (Johnius belengerii) Frame [30] Catla catla Visceral organs [31] Sturgeon Visceral organs [32] Tuna Liver by-products [33] Alaska pollock Frames/backbones [34] Skate Skin [35] Cod (Gadus macrocephalus) Skin [36] Channa striatus Roe [37] Bluefin tuna Head [38] Salmon Pectoral fin [39] Seabass Skin [40] Leatherjacket Head waste [41] Japanese threadfin bream Frame waste [42] Rainbow trout By-products [43] Squid By-products [44] Leiognathus splendens By-catch [45] Salmon By-products [46] Monkfish By-products like head and viscera [47] Turbot By-products [48] Fish Solid and liquid waste generated from processing operations [49]…”
Section: Fish Secondary Raw Materials Referencementioning
confidence: 99%